Modeling the impact of social discrimination on the physical and mental health of portuguese gay, lesbian and bisexual people - Pereira, Henrique Marques (2016)
Background: Despite growing acceptance of same-sex sexuality in Portugal, identity development of lesbian, gay and bisexual (LGB) individuals is still restricted by negative societal attitudes, which maintain the experience of stigmatization and discrimination. The purpose of this study is to document the frequency of discriminatory events experienced by sexual minorities and their association with indicators of physical and mental health in Portugal. Methods: A total of 610 LGB participants completed an online survey (mean age = 34.48, SD = 11.54). Most participants were single and self-identified as gay (73.8%). The survey included five categories of survey items: demographic information, social support, physical health, mental health, and discrimination experiences. Results: Physical and mental health results revealed that bisexual people were more likely to report higher levels of psychological distress than gay men. Overall, between one-fifth and one-fourth of the participants in this sample frequently felt the need to hide their sexual orientation to prevent discrimination experiences across the different settings. Regarding actual discrimination experiences, close to 20% reported having suffered from verbal abuse, followed by close to 10% who suffered from written threats, harassment, and physical threats. A hierarchical multiple regression analysis was performed to assess the effects of anticipated and actual discrimination on mental health. Possible confounding variables were added in the first block – age, sexual orientation, being in a relationship, body mass index, and HIV status. Anticipated and actual discrimination experiences were added in the second block. The first block of the analysis explained 6% of the overall variance, while the second block – discrimination experiences – explained an additional 17%. Conclusion: Portuguese culture and stigma/discrimination create discriminatory experiences which impact LGB people’s health. Unless policies are changed to allow for the acceptance of LGB people, they will continue to experience violence and discrimination as a result of homophobia.